Strategi Dinas Perpustakaan dan Arsip Daerah (DPAD) Provinsi Jambi dalam Mengembangkan Perpustakaan Berbasis Inklusi Sosial untuk Mewujudkan Masyarakat Literate - Khairunisa, Khairunisa; Dastina, Wenny; Katutu, Buchari (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2020)
ABSTRACT Introduction. The purpose of this study was to determine the Jambi Province DPAD Strategy in developing a Social Inclusion-Based Library to Create a Literate Society, constraining factors in developing a social inclusion-based library in an effort to create a literate community in the Jambi Province Regional Library and Archives Service, and the efforts made to overcome these obstacles. Data Collection Metod. This study used a descriptive qualitative method with a purposive sampling approach. Resilt and Discussions. The results of this study indicate that there are several strategies implemented by DPAD Jambi Province in developing social inclusion in libraries, namely: involving the active role of librarians, issuing policy regulations and forming a Synergy Team, holding stakeholder meetings, Launcing Ipustaka Jambi, and carrying out activities advocacy Peer Learning Meeting. The obstacles faced by the Jambi Province Regional Library and Archives Office in developing social inclusion- based libraries are limited budget funds and networks. As for the efforts made by the Regional Library and Archives Office of Jambi province in overcoming the constraints of developing social inclusion-based libraries, namely establishing cooperation with various parties, both from the province, district and private sector and utilizing the existing budget optimally. Conclusions. Based on the research that has been done on the DPAD strategy in developing a social inclusion-based library. With this strategy, it is hoped that this social inclusion program can run well and can be developed for program development in program recipient libraries, namely district libraries and village libraries. Keyword: Strategi, Inklusi Sosial, Perpustakaan Umum, Masyarakat Literate